BLUE-GREEN INFRASTRUCTURE DISTRIBUTION IN PIAUÍ, BRAZIL - Viezzer, Jennifer; de Moraes, Emidio Neves; Biondi, Daniela (Floresta, 2022)
Studies of blue-green infrastructure (BGI) are still incipient in Brazil. Since its access and benefits may not be well-distributed among the population, it is important to evaluate BGI distribution to base territorial and environmental planning. This is especially true for less urbanized and developed states, like Piauí. Thus, this study aimed to assess urbanization, socioeconomic and BGI parameters in Piauí municipalities. We conducted a quantitative assessment through descriptive and correlation statistical analysis and spatial data visualization considering absolute population, population density, relative built area, and built area per inhabitant as urbanization parameters; per capita income, poverty, GINI inequality, and human development indexes as socioeconomic parameters; and relative forest area, forest area per inhabitant, relative BGI area, and BGI area per inhabitant as BGI parameters. Strong correlations were found between BGI and urbanization, while important but weak correlations were found between BGI and socioeconomic variables. Municipalities with more BGI are less urbanized and have worse socioeconomic conditions. Results reinforce that the urbanization processes of Piauí municipalities need to ensure open spaces for urban BGI, therefore pursuing environmental justice and BGI access and benefits for all.